A Simultaneous Control, Localization, and Mapping System for UAVs in GPS-Denied Environments - Rodrigo Munguia; Antoni Grau; Yolanda Bolea; Guillermo Obregón-Pulido (Drones, 2025)
Unmanned Aerial Vehicles (UAVs) have gained significant attention due to their versatility in applications such as surveillance, reconnaissance, and search-and-rescue operations. In GPS-denied environments, where traditional navigation systems fail, the need for alternative solutions is critical. This paper presents a novel visual-based Simultaneous Control, Localization, and Mapping (SCLAM) system tailored for UAVs operating in GPS-denied environments. The proposed system integrates monocular-based SLAM and high-level control strategies, enabling autonomous navigation, real-time mapping, and robust localization. The experimental results demonstrate the system’s effectiveness in allowing UAVs to autonomously explore, return to a home position, and maintain consistent mapping in virtual GPS-denied scenarios. This work contributes a flexible architecture capable of addressing the challenges of autonomous UAV navigation and mapping, with potential for further development and real-world application.